2011
DOI: 10.1002/anie.201100193
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Assembled M8L6 Cubic Cage that Selectively Encapsulates Large Aromatic Guests

Abstract: Biological encapsulants such as ferritin, [1] lumazine synthase, [2] and viral capsids [3] achieve their selective separation and sequestration of substrates by providing: 1) a guest microenvironment isolated from the surroundings, 2) favorable interactions complementing a size and shape match with the encapsulated guests, and 3) sufficient flexibility to allow guests to be incorporated and released.[4] These biological hosts self-assemble from multiple copies of identical protein subunits, the symmetries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
224
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 376 publications
(233 citation statements)
references
References 56 publications
7
224
0
2
Order By: Relevance
“…Host platforms containing extended p-systems have been designed because of their affinity towards the sphere-like unsaturated structure of fullerenes. In this line, several covalent or supramolecular approaches pursued include: (a) macrocyclic arene-based receptors [18][19][20][21][22][23][24] , (b) macrocyclic structures containing aromatic heterocycles [25][26][27][28] , (c) p-extended TTF receptors [29][30][31][32][33] and (d) macrocyclic or jawlike structures containing porphyrin moieties 17,[34][35][36][37][38][39][40][41][42][43][44][45] . Interestingly, Fujita and co-workers reported the use of the empty channels of a metal-organic framework (MOF) for encapsulating fullerenes upon soaking MOF crystals in fullerene-containing toluene.…”
mentioning
confidence: 99%
“…Host platforms containing extended p-systems have been designed because of their affinity towards the sphere-like unsaturated structure of fullerenes. In this line, several covalent or supramolecular approaches pursued include: (a) macrocyclic arene-based receptors [18][19][20][21][22][23][24] , (b) macrocyclic structures containing aromatic heterocycles [25][26][27][28] , (c) p-extended TTF receptors [29][30][31][32][33] and (d) macrocyclic or jawlike structures containing porphyrin moieties 17,[34][35][36][37][38][39][40][41][42][43][44][45] . Interestingly, Fujita and co-workers reported the use of the empty channels of a metal-organic framework (MOF) for encapsulating fullerenes upon soaking MOF crystals in fullerene-containing toluene.…”
mentioning
confidence: 99%
“…6 Nevertheless, it was also observed that some platinum(II) complexes tend to degrade during photolysis, even due to undesirable reactions caused by the H 2 evolved, leading to dispersion of colloidal platinum nanoparticles. 7 In our hope to improve the robustness of the Pt(II) catalysts during photolysis, the present study focuses on the Pt(II) catalyst encapsulated within the title self-assembled molecular capsule, 8,9 which was reported by others from different perspectives. 1012 In this study, a molecular cube consisting of six metal-free porphyrin fragments (Cube; [C 408 H 276 (Figure 1), reported by Nitschke et al, 9 has been selected as a host framework.…”
mentioning
confidence: 99%
“…9,11 Taking these into consideration, we have selected several platinum(II) complexes having π-conjugated ligand systems, 3,4 such as PtCl 2 (bpy) (PtBpy), PtCl 2 (dmbpy) (PtDmb; dmbpy: 4,4¤-dimethyl-2,2¤-bipyridine), PtCl 2 (phen) (PtPhn; phen: 1,10-phenanthroline), and [PtCl(tpy)] + (PtTpy; tpy: 2,2¤:6¤,2¤¤-terpyridine) ( Figure 2). Based on the method used to encapsulate guest molecules within Cube, 9 Cube was reacted with each catalyst (4 equiv) in DMF (N,N-dimethylformamide) at 80°C for 22 h (see SI for details) followed by nearly quantitative deposition of the Cube components by adding a large excess of ether. Although we were unable to clarify the optimum conditions affording a single product in a quantitative yield, we could successfully confirm that singly and doubly modified Cube's, i.e., Cube(PtCat) and Cube(PtCat) 2 (PtCat = PtBpy, PtDmb, or PtPhn), can be given when a neutral catalyst is employed as a guest molecule (Scheme 2).…”
mentioning
confidence: 99%
“…Platonic or Archimedean metal-organic polyhedra can be constructed by a careful choice of ligands and metal ions (8,(23)(24)(25)(26)(27), where the geometries of the individual building blocks define the symmetry axes of the polyhedron. Although high-symmetry architectures represent a great achievement in terms of logical molecular design, lower-symmetry ones are possibly of still greater interest.…”
mentioning
confidence: 99%
“…Besides the fundamental interest in symmetry breaking mentioned above (1), an asymmetric capsule could achieve recognition of asymmetric substrates (28) and possibly catalyze asymmetric transformations (29). So far all reported metal-organic capsules have high symmetry (27,30,31), although in some cases they are chiral (29,(32)(33)(34), and specific guest molecules are observed to stabilize lower-symmetry structures (32,35). M 4 L 6 capsules are constructed from octahedrally coordinated metal ions and linear bis-bidentate ligands.…”
mentioning
confidence: 99%